The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1371/journal.pone.0188101
|View full text |Cite
|
Sign up to set email alerts
|

Alpha desynchronization/synchronization during working memory testing is compromised in acute mild traumatic brain injury (mTBI)

Abstract: Diagnosing and monitoring recovery of patients with mild traumatic brain injury (mTBI) is challenging because of the lack of objective, quantitative measures. Diagnosis is based on description of injuries often not witnessed, subtle neurocognitive symptoms, and neuropsychological testing. Since working memory (WM) is at the center of cognitive functions impaired in mTBI, this study was designed to define objective quantitative electroencephalographic (qEEG) measures of WM processing that may correlate with cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 89 publications
2
31
1
Order By: Relevance
“…The brain cognitive challenge, or N-back WM test (N = 0, 2 that reflect the load conditions of the task), was administered using E-prime software (Psychology Software Tools, Inc., Sharpsburg PA) on a Dell Precision T5610 with a 20" screen. Procedures were described previously (Arakaki et al, 2018(Arakaki et al, , 2019. Participants were comfortably seated before a computer screen and were instructed, practiced for 2-3 min, and were then tested for 0-back, then for 2-back.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The brain cognitive challenge, or N-back WM test (N = 0, 2 that reflect the load conditions of the task), was administered using E-prime software (Psychology Software Tools, Inc., Sharpsburg PA) on a Dell Precision T5610 with a 20" screen. Procedures were described previously (Arakaki et al, 2018(Arakaki et al, , 2019. Participants were comfortably seated before a computer screen and were instructed, practiced for 2-3 min, and were then tested for 0-back, then for 2-back.…”
Section: Methodsmentioning
confidence: 99%
“…We performed group comparisons on participant baseline characteristics using two-sided t-tests or Fisher's exact test. For each participant, we averaged the total gamma power from all sensors and the gamma power from each sensor for each of the following 6 regions (Lianyang et al, 2016;Arakaki et al, 2018): frontal or F (Fz, F3, F4), central or C (Cz, C3, C4), parietal or P (Pz, P3, P4), left temporal or LT (F7, T3, T5), right temporal or RT (F8, T4, T6), and occipital or O (O1, O2) (demonstrated in the results section). We compared gamma power between two groups (PAT, NAT).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This enables us in concluding that the positive correlation of affect and approach/ withdrawal measures with frontal asymmetry score α α − lpha lpha (ln( ) ln( )) Right L eft is the resultant of left hemispherical neuronal activity and vice versa. However, recently, many neuro-vascular studies [48][49][50][51] have observed alpha-BOLD synchronization wherein the alpha power correlates positively with neural activation during task engagement. Hence, there is a need to fully understand the neurovascular coupling and neural underpinning associated with frontal EEG asymmetry 5 and how alpha-BOLD synchronization or desynchronization during resting-state associates with affect and approach/withdrawal behavior.…”
Section: Right L Eftmentioning
confidence: 99%